(LYS)(16)-based reducible polycations provide stable polyplexes with anionic fusogenic peptides and efficient gene delivery to post mitotic cells. - Parker, A; Eckley, L; Singh, S; Preece, J; Collins, L; Fabre, J (2007)
Extracellular stability, endocytic escape, intracellular DNA release and nuclear translocation of DNA are all critical properties of non-viral vector/DNA particles. We have evaluated a (Lys)(16)-based linear, reducible polycation (RPC) in combination with an acid-dependent, anionic fusogenic peptide for gene delivery to dividing and post-mitotic cells. The RPC was formed from Cys(Lys)(16)Cys monomers. Molecular weight was 24,000 Da, corresponding to an average of 10.5 peptide monomers per RPC. Non-reducible polylysine (PLL) (27,000 Da) and monomeric (Lys)(16) peptide were evaluated for comparison. (Lys)(16)/DNA particles were disrupted at fusogenic peptide concentrations well below those used for gene delivery. By contrast, RPC/DNA an PLL/DNA particles were stable in the presence of high concentrations of the anionic peptide. Addition of 10% serum virtually abolished the transfection ability of (Lys)(16)/DNA/fusogenic peptide particles, but had little effect on RPC/DNA/fusogenic peptide particles. RPC/DNA/fusogenic peptide particles were highly effective for gene delivery to both cell lines and post-mitotic corneal endothelium. PLL/DNA/fusogenic peptide particles were moderately effective on cell lines, but gave no gene delivery with corneal endothelial cells. We conclude that (Lys)(16)-based RPC/DNA/fusogenic peptide particles provide a gene delivery system which is potentially stable in the extracellular environment and, on reductive depolymerisation, can release DNA plasmids for nuclear translocation.